A TV em Pânico: o enquadramento das celebridades no Pânico na TV - Leonardo Gomes Pereira (2009)
This work aims at the analysis of the framing that a television show Pânico na TV shapes to deal with the universe of celebrities, in other words, the meanings, the values and the positions that the program stablishes to the world of the famous. Besides that, this work intends to notice the relationship between this framing and features of the social-cultural situation of a public, as the work is inscribed in a relational perspective. Within this perspective, we present the search we made for the most adequate theories, concepts and mathodology. The references that guide the way we comprehend television are presented in two complementary axis: the history of television as a technological aparatus and as a form of relationship that attends, at the same time that helps to create, social and cultural demands. After situating the humouristic proposition of the show ins a historical configuration of a field of possibilities that permits its existence, we present our comprehension of humour as a social linkage and as a cultural indicative, as well as theforms it seems to gain in the show, such as parody, irony and satire. We then go on to our comprehension of the concept of celebrities, as it presents itself in the contemporary scene of the increasing in value of mediatic visibility and of the symbolic products selfproduction and self-distribution technologies. As a methodology, we have a path composed of mutually imbricated phases, that we use to analyse four editions of the show: the analysys of the context that the phenomenom is inscribed; the characterization of the object as a significatve form; a content analysis; and the framing analysis of four emblematic cases of interaction between the show and four different types of celebrities (a celebrity wannabe, a opportunist recent-celebrity, an ex-celebrity and a reknown clebrity). We could perceive though the plurality of framings with which the show works and how the are linked with the wider proposition and values of Pânico na TV.